Active Modulation of Graphene Near‐Infrared Electroabsorption Employing Borophene Plasmons in a Wide Waveband. Issue 6 (10th January 2022) - Nong, Jinpeng; Feng, Fu; Gan, Jiaan; Min, Changjun; Yuan, Xiaocong; Somekh, Michael
Abstract: The unique optical and electronic properties of 2D materials make them suitable for the design of novel optoelectronic devices with ultracompact sizes, exhibiting great potential for major advances in the state of art of existing techniques. Here, for the first time, a prototype of a modulator is theoretically presented for the active modulation of graphene electroabsorption enabled by the tunable anisotropic borophene plasmons. Simulations reveal that the strong localized electrical field induced by borophene plasmons can significantly improve the graphene electroabsorption, of which the center wavelength can be further dynamically controlled by gate tuning the resonant wavelength of borophene plasmons. Then by gate tuning the graphene Fermi energy to transform graphene between a lossy and a lossless material, electrically switched absorption of graphene with modulation depth of 100% can be realized within a wide waveband in the near‐infrared region, including the commercially important telecommunication wavelength of 1.55 µm, indicating the excellent performance of the designed modulator via such mechanism. Such wavelength‐tunable graphene electroabsorption modulation strategy based on borophene plasmons provides an effective method for the design of graphene‐based selective multichannel switches or modulators, which is unavailable in previous reported strategies that can be only realized by passively changing the structural parameters. Abstract : A prototype modulator is designed for the active modulation of graphene electroabsorption employing anisotropic borophene plasmons. The center wavelength of graphene electroabsorption can be dynamically controlled by tuning borophene plasmonic resonant wavelength. High modulation depth of 100% can be achieved within a wide near‐infrared region by gate tuning graphene Fermi energy to transform graphene between a lossy and a lossless material.